Control of the Process of Cutting Metals by the Power Consumption of the Electric Motor of the Metal-Cutting Machine - Eldor Tursunovich Mamurov (Genius Publishing Group, 2022)
The article deals with the issues of control of the metal cutting process by the power consumption of the electric motor of the machine tool and its use as an informative parameter in the creation of high-performance technologies for processing machine parts in automated production.
Keywords: cutting process; cutting power; control system; cutting force